The role of recent refugees' educational selectivity in their children's educational decisions in Germany - Welker, Jörg; Will, Gisela (Frontiers in Sociology, 2023)
This paper uses the example of newly arrived refugees to examine the role of recent migrants' educational selectivity in their children's educational decisions in Germany. Building on a theoretical model that understands participation in the educational system as the sum of investment decisions of rational individuals, we assume that positively selected parents are more ambitious about having their children admitted to higher-level secondary schools. The role of parental educational selectivity should be particularly pronounced in federal states in which school administrations allow for greater parental involvement. We use data from the first and second face-to-face interviews of the Refugees in the German Educational System (ReGES) project, with an analytical sample of 1,437 adolescents who came to Germany from Syria, Iraq, Afghanistan, and Iran between 2014 and 2017. To generate a household-level index of educational selectivity, we furthermore rely on various country-of-origin-specific data that we aggregate as reference educational distributions. We run linear probability regression models to analyze the role of parents' educational selectivity in adolescents' school placement. Our findings suggest that parental educational selectivity is beneficial beyond parents' absolute educational levels for adolescents' higher-level school placement. Among the five German federal states represented in our analytical sample, the role of parental selectivity is particularly pronounced in two federal states in which parents are provided with greater possibilities to become involved in their children's educational decisions.